High antioxidant foods protect against oxidative stress during acute exhaustive exercise in athletes - Watson, T.; Callister, R.; Taylor, R.; Sibbritt, D.; MacDonald-Wicks, L.; Garg, M. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
Foods high in antioxidants are considered to play a major role in defending the body against oxidative stress during exercise. To determine the role high-antioxidant (HAO) foods play in antioxidant defence mechanisms during exercise we restricted HAO foods in 17 athletes exercised to exhaustion and observed antioxidant and oxidative stress markers. Participants habitually followed HAO diets prior to an initial exercise test and then followed a two-week low-antioxidant (LAO) diet before a second exercise test. The LAO diet induced a 3-fold reduction in the intake of analysed antioxidant nutrients when compared to the HAO diet. During both exercise tests blood samples were taken at pre-exercise, during sub-maximal exercise, post exhaustion and with one hour of recovery. F2-isoprostane concentration (marker of oxidative stress) was significantly higher during sub-maximal exercise (38%), at exhaustion (45%) and after one hour of recovery (31%) when following the LAO diet compared to the HAO diet. Despite the increase in oxidative stress, exercise performance was not affected by the LAO diet. Total antioxidant capacity and individually measured blood antioxidants tended to be lower when following the LAO diet but were not statistically significant. The results indicate that individuals participating in exercise may require higher intakes of exogenous antioxidants to defend against increased oxidative stress during exercise; and that increased requirements can be met through an adequate intake of HAO foods. Thus, there seems no valid reason to widely recommend antioxidant supplements to athletes unless that athlete is consuming a LAO diet for prolonged periods.